Game is the main activity of children - Iltifat Bahadirovna Khakimova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article discusses the influence of play activity on the development of children, considers some pedagogical views of famous scientists and teachers on the play activity of children